High performance anode with dendritic porous structure for low temperature solid oxide fuel cells - Shao, Xin; Rickard, William; Dong, Dehua; Dang, H.; Saunders, M.; Dodd, A.; Parkinson, G.; Li, Chun-Zhu (Elsevier Ltd, 2018)
© 2018 A dendritic porous supported microstructure simultaneously creates small pore size and broad gas diffusion pathways in a solid oxide fuel cell anode membrane. This microstructure also achieves pore sizes that reduce with increasing depth within the membrane without increasing the structure tortuosity. Such a microstructure supplies high triple phase boundary density, fast gas diffusion and low polarization resistance. Here we characterise the performance of a porous anode with such a dendritic microstructure. The solid oxide fuel cell with this high performance anode achieved 0.92 W cm-2 power density at 600 °C.